AASHTO guide specifications for LRFD seismic bridge design (American Association of State Highway and Transportation Officials, 2011)
Covers seismic design for typical bridge types and applies to non-critical and non-essential bridges. Approved as an alternate to the seismic provisions in the AASHTO LRFD Bridge Design Specifications. Differs from the current procedures in the LRFD Specifications in the use of displacement-based design procedures, instead of the traditional force-based R-Factor method. Includes detailed guidance and commentary on earthquake-resisting elements and systems, global design strategies, demand modeling, capacity calculation, and liquefaction effects. Capacity design procedures underpin the Guide Specifications' methodology; includes prescriptive detailing for plastic hinging regions and design requirements for capacity protection of those elements that should not experience damage.
"Publication code: LRFDSEIS-2."
"This second edition of the Guide Specifications for LRFD Seismic Bridge Design includes technical content approved by the Highways Subcommittee on Bridges and Structures through 2011. In addition to revising the first edition content, he authors have added Appendix B, Design Flowcharts."--Preface, p. vii.
Keywords: Bridges -- Design and construction -- Specifications -- United States.; Bridges -- Earthquake effects.; Earthquake resistant design.; elektronické knihy; electronic books